Ameliorating and protective potential of 1-isothiocyanato-4-methyl sulfonyl butane on cisplatin induced oligozoospermia and testicular dysfunction via redox-inflammatory pathway: Histomorphometric and immunohistochemical evaluation using proliferating cell nuclear antigen - Sunday Aderemi Adelakun; Olalekan Wasiu Akintunde; Sikirullai Olatunde Jeje; Oluwatoyosi Abigeal Alao (Elsevier, 2022)
Background: 1-isothiocyanato-4-methyl-sulfonyl (SFN) butane is a naturally occurring compound from broccoli. Cisplatin (CP) reported has a standard chemotherapeutics agent. This study focused on the impact of SFN on cisplatin-induced testicular dysfunctions. Method: Ninety adult-male Sprague-Dawley rats were randomly divided into nine groups of ten (n = 10) rats each. Group A (control) received normal saline, group B received a single dose of 10 mg/kg CP (i.p.), group C received 50 mg/kg bwt of SFN, group D received 100 mg/kg bwt of SFN, group E received 10 mg/kg bwt CP and 50 mg/kg bwt of SFN, group F received 10 mg/kg bwt CP and 100 mg/kg bwt of SFN, group G received 10 mg/kg bwt CP and 50 mg/kg bwt vitamin C, group H received 50 mg/kg bwt of SFN and 10 mg/kg bwt CP, group I received 100 mg/kg bwt of SFN and 10 mg/kg bwt CP. The procedure lasted for 56 days. Testicular histology, and other parameters such as sperm, luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone (TT), reduced glutathione (GSH), glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase (SOD), inflammatory markers, Caspase 3, adrenal and steroidogenic enzymes and corticosterone were investigated. Results: Cisplatin depleted the germ cells and arrest spermatogenesis; reduced the sperm quality, LH, FSH, TT, SOD, CAT, GPx, GSH, 3β-hydroxysteroid dehydrogenase and 17β-hydroxysteroid dehydrogenases and Jonhsen score (JS) and increased lipid peroxidation, IL-1β, TNF-α, IL-6, NF-ĸB, NO and iNOS, caspase-3, adrenal 3-HSD and corticosterone and damage score (DS). Treatment with SFN increased hormonal, antioxidant, and JS, and reduced lipid peroxidation, inflammatory makers, caspase-3, adrenal 3-HSD, and corticosterone and DS. Conclusion: SFN thus provides protective effects against CP-induced testicular dysfunctions in rats.